Model of Company’s Social Sustainability - Oželienė, Danguolė (Socialiniai tyrimai, 2018)
Due to an excessive focus towards economic and environmental dimensions, sustainable development loses the essence of holisticity. Establishing long-term business success requires effective social activities which are of equal importance as economic ones. In the past the tendency of businesses that were avoiding participation in active search of solutions of social problems was justified by the lack of resources and competences in the social field. However, the idea of creating a shared value has proved that solving social problems is financially beneficial for businesses. Yet the social dimension has not been defined distincly, and its content has not been clearly expressed. As a consequence, companies struggle to identify the content and tools of the social dimension themselves. The aim of this article is to create a model for the social dimension of enterprise sustainable development and to develop an indicators system available for quantitative assessment of the social dimension. The result of the research carried out was the critical evaluation of scientific publications, the content of the social dimension of sustainable development was analyzed. A hierarchical system of indicators has been developed for quantitative evaluation using Pareto’s rule and a model for the social dimension of sustainable development of the company was created.